Coordinating teamplay using named locations in a multilingual game environment - Playing esports in an educational context. Issue 2 (3rd April 2022) - Rusk, Fredrik; Ståhl, Matilda
ABSTRACT: This study investigates the video game play of a multiplayer first-person shooter, Counter-Strike: Global Offensive, as part of an esports programme at a vocational school. The game environment is multilingual, and the focal participants are all Finnish-Swedish bilinguals who are proficient in English. The study focuses on the action of providing callouts, which are coordinated English words that refer to specific in-game locations and, when provided, point to opponents' locations. The aim is to investigate how participants employ callouts as part of their in-game interaction and teamplay, and what they orient to as 'callout competence'. With a greater understanding of the social organisation of the multilingual game environment and actions, such as callouts, we can better understand the affordances for collaborative and multilingual learning that games can provide for education. Callout competence appears to align with skills and knowledge that may be transferrable into the educational setting; that is, the components that are part of callout competence require collaborative skills and multilingual competence. These skills are part of what makes the teamwork work, as well as an inherent part of activities in an esports education programme that has broadened the classroom to encompass esports game play outside of the classrooms.